Effects of mindfulness meditation on trait mindfulness, perceived stress, emotion regulation, and quality of life in hemodialysis patients: A randomized controlled trial - Hossam Alhawatmeh; Sami Alshammari; Jehad A. Rababah (Elsevier, 2022)
Objective: This study aimed to examine the effects of mindfulness meditation on trait mindfulness, perceived stress, emotion regulation, and quality of life in end-stage renal disease patients undergoing hemodialysis. Methods: An experimental study with repeated measures design was conducted among a sample of 74 end-stage renal disease patients undergoing hemodialysis between January and May 2021 in the dialysis center at Jahra hospital, Kuwait. The patients were randomly assigned to the experimental (n = 37) and control groups (n = 37). The experimental group participated in 30-min mindfulness meditation sessions (three sessions a week for five weeks) held during their hemodialysis sessions; the participants in the control group were instructed to sit with their eyes closed and relaxed for 30 min three times a week for five weeks during hemodialysis sessions. The dependent variables of both groups were measured at baseline (T0), middle of intervention (T1), and end of intervention (T2) using the Mindful Attention Awareness Scale (MAAS), Perceived Stress Scale (PSS), Emotion Regulation Questionnaire (ERQ), and Kidney Disease Quality of Life (KDQOL-36) questionnaire. The study was registered in the ClinicalTrial.gov (Identifier: NCT05176730). Results: The repeated measures ANOVA (within-subject) results for the experimental group showed that mindfulness meditation had significantly decreased perceived stress by the end of the intervention. Also, mindfulness meditation improved mindfulness, emotion regulation, and kidney disease-related quality of life in the experimental group, and this improvement occurred significantly at both T1 and T2. The repeated measures ANOVA (within and between-subject) results showed that the experimental group, as compared to the control group, had lower perceived stress, higher trait mindfulness, higher emotional regulation, and higher kidney disease-related quality of life over time. Conclusions: The positive findings of this study offer health policy-makers and hospital administrators a promising tool to use with patients undergoing hemodialysis as a way to manage stress and improve quality of life. However, this study should be replicated in multiple settings with follow-up assessments.